2005
DOI: 10.1143/jjap.44.4092
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Beam Induced Liquid Crystal Alignment on Diamond-like Carbon and Fluorinated Diamond-like Carbon Thin Films

Abstract: Homogeneous and homeotropic orientations of nematic liquid crystal (NLC) are investigated on various inorganic thin films which are exposed to Ar ion-beam. It is the novel investigations which results in a completely dry processing technique for both the thin film deposition and alignment steps. In the case of homogenous alignment on diamond-like carbon (DLC) layer, optical band gap and the polar surface energy are investigated in order to elucidate the alignment mechanism by ion beam (IB) irradiation. We eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…It has been known that the high pretilt angles of LC molecules required to produce homeotropic alignment are related to the low surface energy values of the alignment layer and/ or the steric repulsions between the LC molecules and the alignment layers. 36,[49][50][51][52][53][54][55][56] Therefore, polyimides having long alkyl side groups have been widely used to align LCs perpendicular to the surface of the alignment layer, because the long alkyl groups can produce low surface energy layers due to their steric effect. 51,56 We also found that the LC alignment behavior on the polystyrene derivatives in this study could be ascribed to the surface energy values.…”
Section: Resultsmentioning
confidence: 99%
“…It has been known that the high pretilt angles of LC molecules required to produce homeotropic alignment are related to the low surface energy values of the alignment layer and/ or the steric repulsions between the LC molecules and the alignment layers. 36,[49][50][51][52][53][54][55][56] Therefore, polyimides having long alkyl side groups have been widely used to align LCs perpendicular to the surface of the alignment layer, because the long alkyl groups can produce low surface energy layers due to their steric effect. 51,56 We also found that the LC alignment behavior on the polystyrene derivatives in this study could be ascribed to the surface energy values.…”
Section: Resultsmentioning
confidence: 99%
“…Homogeneous alignment with a controllable pretilt angle of 0 to 10 (from horizontal) and strong anchoring is achieved. Homeotropic alignment was reported a few years later [52], using fluorinated diamond-like-carbon. Again, controllable pretilt angles from 71 to 89.8 could be produced.…”
Section: ) Oblique Evaporation Of Inorganic Alignment Layersmentioning
confidence: 91%
“…The planes of the remaining rings are predominantly parallel to the direction of the ion beam and will thus induce alignment of the liquid crystal molecules [53]. For the homeotropic alignment the mechanism is less clear, although the fluorohydrocarbons are believed to contribute to the vertical alignment by means of their extremely low surface tension [52].…”
Section: ) Oblique Evaporation Of Inorganic Alignment Layersmentioning
confidence: 99%
“…Since the polydimethylsiloxane (PDMS) surface provides a low surface energy and hydrophobicity [7], the LC alignment induced by the PDMS surface was first examined. It is known that a surface with low hydrophobicity aligns the LC vertically [8,9]. An LC cell with two PDMS substrates was prepared as shown in the left diagram in Fig.…”
Section: Construction Of a Transflective Lcd With A Dual-gap Substratementioning
confidence: 99%